Constituting economic and social rights - Young, Katharine G. (Oxford : Oxford University Press, 2012)
Food, water, health, housing, and education are fundamental to human freedom and dignity, yet only recently have legal systems begun to secure these fundamental individual interests as rights. This book analyses the transformation of socio-economic rights into constitutional rights, and their impact on public law and constitutional theory.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Includes bibliographical references and index.
Keywords: Basic needs -- Law and legislation; Social rights